Implementation of Line Follower Robot based Microcontroller ATMega32A - Abdul Latif; Hendro Agus Widodo; Robbi Rahim; Kunal Kunal (Journal of Robotics and Control (JRC), 2020)
The development of technology in the field of robotics is very fast, but in the eastern regions of Indonesia, namely the development of the development has not yet felt the impact. Especially in the university's electrical laboratory Musamus Merauke learning media devices for microcontrollers are also not yet available, therefore the author wants to pioneer by implementing the simplest robot design, the line follower robot, where the robot only goes along the lines. This study uses an experimental method, by conducting a research process based on sequences, namely: needs analysis, mechanical chart design, electronic part design and control program design, manufacturing, and testing. The line follower robot based on ATmega32A microcontroller has been tested and the results show that the line follower robot can walk following the black line on the white floor and can display the situation on the LCD. But this line follower robot still has shortcomings in the line sensor sensitivity process depending on a certain speed. At speeds of 90-150 rpm the line follower robot can follow the path, while more than 150 rpm the robot is not able to follow the path.